Educational Leadership’s Motivational Strategies for Transformational Growth of Teachers: A Comparative Analysis of Public and Private Schools - Sohail, Amir; Khan, Bazgha Saleem; Raza, Shahid (Pakistan Journal of Humanities and Social Sciences, 2023)
The present study talked about educational leaders of our educational sectors. Emphasize was not only laid on their role but it also negotiated their impact towards character building of students and later, communal benefits. Little grain of learning had always made a beautiful land for practice for those learnt strategies i.e., security, alertness, progress, upgradation, growth, maturity and transformation. Role of educational leaders is about, how they motivated their sub-ordinates and transformed them altogether. Survey method was adopted through which data was gathered from the purposive sample of secondary level teachers (N=150), from the public/private schools, those belong to city Okara, all public/private school teachers as, population. For rationalization of researchable questions, construction of a questionnaire was made with large proportion having restricted response. Quantitively analyzed results presented significant difference on transformational growth of teachers from public and private schools. It was also observed that private schools had better setup for awarding incentives, upgradation, behavior, environment, security, insurance, motivation and instructional aids that had positive impact on the leadership as well helped student to be mindful.